Intra uterine device on the severity of recurrent aphthous stomatitis: A case report - Anitasari, Merry; Marlina, Erni; Usman, Nur A.; Putri, Andi AM.; Israyani, Israyani; Yusran, Ali; Rahmi, Rahmi (Hasanuddin University, 2024)
Objectives: This article aimed to report RAS with severe clinical form due to hormonal fluctuant triggered by Intra Uterine Device.Methods: A 26-year-old female patient came to Hasanuddin University Dental Hospital with complaints of continuous mouth ulcers since 1 year ago. Deep anamnesis revealed that the initial trigger of the unhealed ulcers incidentally happened at the same time after the patient installed an Intra Uterine Device (IUD) which also led to continuous menstruation in the past month leading to self-decision to have her IUD removed. Due to her clinically anemic condition, the patient was referred for routine blood examination with the result of lower red blood cells and hemoglobin which also contributed to the ulcer severity. Since the main cause of hormonal imbalance has been removed, supportive treatment uses vitamins to support the patient’s systemic condition which gives a good response.Conclusion: Recalcitrant and severe intraoral ulceration may be triggered by hormonal imbalance caused by IUD. Removal of these devices can help reduce oral complaints if the patient is on optimum health, otherwise, the background systemic needs to be improved.